2011
DOI: 10.5402/2011/539503
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nonsentinel Nodal Involvement to Aid Intraoperative Decision Making in Breast Cancer Patients with Positive Sentinel Lymph Nodes

Abstract: Background. Up to 60% of patients with a positive sentinel lymph node (SLN) have no additional nodal involvement and do not benefit from completion axillary lymph node dissection (ALND). We aim to identify factors predicting for non-SLN involvement and to validate the MSKCC nomogram and Tenon score in our population. Methods. Retrospective review was performed of 110 consecutive patients with positive SLNs who underwent ALND over an 8-year period. Results. Fifty patients (45%) had non-SLN involvement. Non-SLN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Following the MSKCC model described by Van Zee et al, many models have been proposed and tested by many studies (Van Zee et al, 2003;Kocsis et al, 2004;Degnim et al, 2005;Smidt et al, 2005;Soni et al, 2005;Lambert et al, 2006;Alran et al, 2007;Ponzone et al, 2007;Cho et al,. 2008;Klar et al, 2008;Kohrt et al, 2008;Pal et al, 2008;Poirier et al, 2008;Coufal et al, 2009;Coutant et el., 2009;Scow et al, 2009;Gur et al, 2010;Moghaddam et al, 2010;Lombardi et al, 2011;Hessman et al, 2011;Hidar et al, 2011;Tan et al, 2011;Chen et al, 2012;Derici et al, 2012;Zhu et al, 2012;Sasada et al, 2013). The last proposed international model from multiple centers in Europe, however, has not been validated to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the MSKCC model described by Van Zee et al, many models have been proposed and tested by many studies (Van Zee et al, 2003;Kocsis et al, 2004;Degnim et al, 2005;Smidt et al, 2005;Soni et al, 2005;Lambert et al, 2006;Alran et al, 2007;Ponzone et al, 2007;Cho et al,. 2008;Klar et al, 2008;Kohrt et al, 2008;Pal et al, 2008;Poirier et al, 2008;Coufal et al, 2009;Coutant et el., 2009;Scow et al, 2009;Gur et al, 2010;Moghaddam et al, 2010;Lombardi et al, 2011;Hessman et al, 2011;Hidar et al, 2011;Tan et al, 2011;Chen et al, 2012;Derici et al, 2012;Zhu et al, 2012;Sasada et al, 2013). The last proposed international model from multiple centers in Europe, however, has not been validated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tested these models and have obtained varying results (Van Zee et al, 2003;Kocsis et al, 2004;Degnim et al, 2005;Soni et al, 3 2005; Lambert et al, 2006;Ponzone et al, 2007;Pal et al, 2008;Kohrt et al, 2008;Cho et al, 2008;Klar et al, 2008;Poirier et al, 2008;Coufal et al, 2009;Coutant et el., 2009;Scow et al, 2009;Gur et al, 2010;Moghaddam et al, 2010;Hessman et al, 2011;Hidar et al, 2011;Lombardi et al, 2011;Tan et al, 2011;Derici et al, 2012;Chen et al, 2012;Zhu et al, 2012;Sasada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, various mathematical models have been developed in an attempt to predict the subgroup of patients who despite having positive SLNs will not require axillary dissection because their risk of additional nodal disease is low. The MSKCC model19 is one of the more well-received and validated nomograms in various populations 9 18 20 26–32. In our study, we have validated the MSKCC nomogram in our study population as well, with the AUC values of the original MSKCC nomogram being 0.76 compared with ours of 0.716 (95%CI 0.653–0.779).…”
Section: Discussionmentioning
confidence: 99%
“…Several mathematical models have been described in the literature, but the most widely validated model remains that of the Memorial Sloan-Kettering Cancer Centre (MSKCC) nomogram,7 18 published by Van Zee et al 19 in 2003 and which can be found on the MSKCC website (http://nomograms.mskcc.org/Breast/BreastAdditionalNonSLNMetastasesPage.aspx). The MSKCC nomogram has been validated in several populations worldwide, but to date only one group has tested it in the Singaporean population, with a cohort of 110 patients 20. In our current study, we aim to validate the MSKCC nomogram in a larger cohort of patients managed at our institution in order to ascertain its reproducibility and ease of use, as well as to identify if different parameters might be able to improve the predictive value of the nomogram.…”
Section: Introductionmentioning
confidence: 99%